Mixed convection flow past through a stretching cylinder with heat generation/absorption and convective boundary condition - Sakidin, H. (American Institute of Physics Inc., 2016)
We have examined the impact of mixed convection with heat generation/absorption and convective boundary condition over a stretching cylinder. We simplified the PDEs into ODEs with the help of appropriate similarity transformation. Resulting ODEs are then solved numerically with Bvp4c method. We examined the effect of different flow parameters on velocity and temperature distribution graphically. Further, calculated the numeric values of physical interested parameters such as skin friction coefficient and Nusselt number against all involved parameters. The skin friction coefficient depict decline for Biot number and heat generation/absorption parameter whereas the heat transfer rate decreases with heat generation/absorption but increases for Biot number. Â© 2016 Author(s).